Increasing habitual walking in mobility-limited older adults through a personalized GIS-based intervention - R. Schilling; R. Weibel; E. Giannouli; D. Infanger; A. Sofios; S. Gisler; C. Röcke; T. Rantanen; E. Portegijs; C. Schuster-Amft; A. Mai; A. Schmidt-Trucksäss; et al. (Bern Open Publishing, 2024)
Background Ample evidence supports the health benefits of low-intensity physical activity such as walking, which is universally accessible and impacted by neighbourhood environmental factors like green spaces and availability of local amenities. Aim The MOBITEC-Routes project will investigate the effects of an individualized GIS-based walking intervention on physical and psychosocial functioning in mobility-limited older adults. Methods A randomized controlled trial to promote habitual walking will take place. The sample will include 130 inactive, chronically ill, mobility-limited older adults. The intervention will combine professional consultations with map-based planning and behaviour change techniques derived from the Health Action Process Approach. Results Expected outcomes include increase in participants' daily step count, physical activity levels, physical function, life space mobility, self-efficacy, social participation, and quality of life. Conclusion MOBITEC-Routes is poised to offer new insights into personalized GIS-based interventions' effectiveness in improving mobility and overall well-being in older adults with mobility impairments.